Effect of application of transcranial direct current stimulation during task-related training on gait ability of patients with stroke - Park, Seong Doo; Song, Hyun Seung; Kim, Jin Young (Journal of Physical Therapy Science, 2015)
[Purpose] The objective of this study was to determine the effect of transcranial direct current stimulation (tDCS) during task-related training (TRT) on the gait ability of patients with chronic stroke. [Subjects and Methods] The participants were 24 patients who were diagnosed with hemiplegia due to stroke. Three groups were created: subjects who performed TRT for general exercise therapy (TRT), subjects who received sham tDCS during TRT for general exercise therapy (TST), and subjects who received tDCS during TRT for general exercise therapy (TT). [Results] The stance phase symmetry profile, the swing phase symmetry profile, and gait velocity all decreased significantly in the TT group compared with the TRT group. However, there was no significant difference in the step length symmetry profile among the groups. [Conclusion] A application of tDCS, that affects the excitatory regulation in the cortical motor area, is an effective rehabilitation method for gait improvement.